Identification of beryllium-dependent peptides recognized by CD4(+) T cells in chronic beryllium disease - Falta, Michael T. (The Rockefeller University Press, 2013)
Chronic beryllium disease (CBD) is a granulomatous disorder characterized by an influx of beryllium (Be)-specific CD4(+) T cells into the lung. The vast majority of these T cells recognize Be in an HLA-DP–restricted manner, and peptide is required for T cell recognition. However, the peptides that stimulate Be-specific T cells are unknown. Using positional scanning libraries and fibroblasts expressing HLA-DP2, the most prevalent HLA-DP molecule linked to disease, we identified mimotopes and endogenous self-peptides that bind to MHCII and Be, forming a complex recognized by pathogenic CD4(+) T cells in CBD. These peptides possess aspartic and glutamic acid residues at p4 and p7, respectively, that surround the putative Be-binding site and cooperate with HLA-DP2 in Be coordination. Endogenous plexin A peptides and proteins, which share the core motif and are expressed in lung, also stimulate these TCRs. Be-loaded HLA-DP2–mimotope and HLA-DP2–plexin A4 tetramers detected high frequencies of CD4(+) T cells specific for these ligands in all HLA-DP2(+) CBD patients tested. Thus, our findings identify the first ligand for a CD4(+) T cell involved in metal-induced hypersensitivity and suggest a unique role of these peptides in metal ion coordination and the generation of a common antigen specificity in CBD.